Distal Enhanced Sedimentation From Volcanic Plumes: Insights From the Secondary Mass Maxima in the 1992 Mount Spurr Fallout Deposits. Issue 10 (21st October 2017) - Eychenne, Julia; Rust, Alison C.; Cashman, Katharine V.; Wobrock, Wolfram
Abstract: Some tephra fallout deposits show an increase of mass and thickness at distances from the source >100 km (areas of secondary mass maximum, ASMM) which demonstrates distal enhanced sedimentation from volcanic plumes. We explore development of the ASMMs during the 1992 August and September Mount Spurr eruptions, USA, by combining field data on the spatial distribution of mass and grain size with (1) simulations of individual particle settling through a homogeneous and horizontally stratified atmosphere and (2) mesoscale models of the three‐dimensional wind field that include the effect of the underlying topography. The crosswind and downwind variations of deposit characteristics indicate that the increase of sedimentation at the ASMMs is not formed solely because of preferential settling of small ash particles (<125 μm), as commonly assumed in aggregation models. Instead, ASMM grain sizes correspond to the fine modes of the bimodal total grain size distributions. There also appears to be a link between the ASMM and the topography: the mass local minima occur across the windward flank of 2 km high mountain ranges, while the ASMMs spread on the leeward flank. Mesoscale models of the three‐dimensional wind field show vertical oscillations in the wind over mountainous regions which may enhance mechanisms of en masse sedimentation (aggregation, hydrometeor formation, and particle boundary layers), as well as strong spatial variations of the horizontal wind field in the lower troposphere. Our study demonstrates the importance of using grain size, as well as mass, data to constrain the complex processes responsible for particle sedimentation from volcanic plumes. Key Points: Areas of secondary mass maximum (ASMM) in tephra fallout deposits do not always result from preferential settling of ash <125 μm in size relative to coarser grain sizes Bimodal total grain size distributions of eruptions can affect the sedimentological pattern of the tephra fallout deposits Topography‐induced perturbations of the wind field generate turbulence above rough terrain, which can accelerate the transfer of particles toward the low atmospheric layers